Time for revolution/by Antonio Negri;translated by Matteo Mandarini - "Negri, Antonio" (London, 2005)
Antonio Negri wrote the two essays that comprise Time for Revolution while serving a prison sentence for alleged involvement with radical left-wing groups. Although the essays were written two decades apart, their concerns are the same: is there a place for resistance in a society utterly subsumed by capitalism? In the wake of the global crisis of capitalism heralded by the 2008 crash, the question has never been more relevant and Negri remains an insightful and passionate guide to any attempt to answer it.
Keywords: Globalization - economic aspects